1990
DOI: 10.1007/bf00965909
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of kappa1 and kappa2 opioid binding sites in frog (rana esculenta) brain membrane preparation

Abstract: The distribution and properties of frog brain kappa-opioid receptor subtypes differ not only from those of the guinea pig brain, but also from that of the rat brain. In guinea pig cerebellum the kappa 1 is the dominant receptor subtype, frog brain contains mainly the kappa 2 subtype, and the distribution of the rat brain subtypes is intermediate between the two others. In competition experiments it has been established that ethylketocyclazocine and N-cyclopropylmethyl-norazidomorphine, which are nonselective k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…One of the salient findings from this body of work is that amphibian brain expresses kappa -like opioid binding sites, as its competitive binding profile was most correlated to the selectivity profile of the mammalian kappa opioid receptor. The main difference observed was a greater affinity of mu and delta selective opioids for the amphibian kappa -like site, and a lesser affinity for kappa -selective opioids, compared to mammalian kappa opioid receptors (143, 132). These results provided the first hint from radioligand studies that opioid receptors in non-mammalian species may be less selective than their mammalian counterparts.…”
Section: Opioid Receptors In Non-mammalian Vertebratesmentioning
confidence: 91%
“…One of the salient findings from this body of work is that amphibian brain expresses kappa -like opioid binding sites, as its competitive binding profile was most correlated to the selectivity profile of the mammalian kappa opioid receptor. The main difference observed was a greater affinity of mu and delta selective opioids for the amphibian kappa -like site, and a lesser affinity for kappa -selective opioids, compared to mammalian kappa opioid receptors (143, 132). These results provided the first hint from radioligand studies that opioid receptors in non-mammalian species may be less selective than their mammalian counterparts.…”
Section: Opioid Receptors In Non-mammalian Vertebratesmentioning
confidence: 91%
“…In heterologous competition experiments it has been found that MERF binds preferentially to the n 2 subtype of opioid receptors and is considered to be the endogenous agonist ligand for those receptors (Attali et al, 1982;Gouarderes and Cros, 1984;Benyhe et al, 1990;Wollemann et al, 1993). Existence of different opioid receptor subtypes are not supported by molecular cloning evidence, but the certainty of them can be explained by heterologous receptor oligomerization that results in altered binding or functional properties (Jordan and Devi, 1999).…”
Section: Met-enkephalin-arg 6 -Phementioning
confidence: 95%
“…Early binding assays in toad and frog brains indicated the presence of µ-, -, and -like opioid-binding sites, and estimated the predominant form of opioid receptor to be -like (60-70%), with considerably fewer µ-and -like sites (20-30%; Simon et al 1982Simon et al , 1984. Since these early studies, numerous reports have characterized multiple ORL receptor types (µ, , ) and subtypes ( 1, 2) in amphibians (Ruegg et al 1980, 1981, Simon et al 1985, Borsodi et al 1986, Makimura et al 1988, Mollereau et al 1988, Benyhe et al 1990, 1992, Newman et al 2002.…”
Section: Introductionmentioning
confidence: 99%